A phylogenomic perspective on diversity, hybridization and evolutionary affinities in the stickleback genus Pungitius. Issue 17 (2nd September 2019) - Guo, Baocheng; Fang, Bohao; Shikano, Takahito; Momigliano, Paolo; Wang, Cui; Kravchenko, Alexandra; Merilä, Juha
Abstract: Hybridization and convergent evolution are phenomena of broad interest in evolutionary biology, but their occurrence poses challenges for reconstructing evolutionary affinities among affected taxa. Sticklebacks in the genus Pungitius are a case in point: evolutionary relationships and taxonomic validity of different species and populations in this circumpolarly distributed species complex remain contentious due to convergent evolution of traits regarded as diagnostic in their taxonomy, and possibly also due to frequent hybridization among taxa. To clarify the evolutionary relationships among different Pungitius species and populations globally, as well as to study the prevalence and extent of introgression among recognized species, genomic data sets of both reference genome‐anchored single nucleotide polymorphisms and de novo assembled RAD‐tag loci were constructed with RAD‐seq data. Both data sets yielded topologically identical and well‐supported species trees. Incongruence between nuclear and mitochondrial DNA‐based trees was found and suggested possibly frequent hybridization and mitogenome capture during the evolution of Pungitius sticklebacks. Further analyses revealed evidence for frequent nuclear genetic introgression among Pungitius species, although the estimated proportions of autosomal introgression were low. Apart from providing evidence for frequent hybridization, the results challenge earlier mitochondrial and morphology‐based hypotheses regarding the number of species and their affinities in this genus: at least seven extant species can be recognized on the basis of genetic data. The results also shed new light on the biogeographical history of the Pungitius ‐complex, including suggestion of several trans‐Arctic invasions of Europe from the Northern Pacific. The well‐resolved phylogeny should facilitate the utility of this genus as a model system for future comparative evolutionary studies.